2016
DOI: 10.1121/1.4971419
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spectral smearing on performance of the spectral ripple and spectro-temporal ripple tests

Abstract: The main aim of this study was to use spectral smearing to evaluate the efficacy of a spectral ripple test (SRt) using stationary sounds and a recent variant with gliding ripples called the spectro-temporal ripple test (STRt) in measuring reduced spectral resolution. In experiment 1 the highest detectable ripple density was measured using four amounts of spectral smearing (unsmeared, mild, moderate, and severe). The thresholds worsened with increasing smearing and were similar for the SRt and the STRt across t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…Bonferroni-corrected pairwise comparisons showed that thresholds were significantly lower (worse) for R ¼ 16 and 32 Hz than for all other values of R. The value of D at threshold was just above 5 RPO for R 8 Hz, consistent with the results of Narne et al (2018) for R ¼ 5 Hz. The median threshold across participants for the condition with static ripples was similar to that reported by Narne et al (2016) and was also similar to the median threshold across participants for the conditions with R ¼ 2-8 Hz.…”
Section: Methodssupporting
confidence: 84%
See 4 more Smart Citations
“…Bonferroni-corrected pairwise comparisons showed that thresholds were significantly lower (worse) for R ¼ 16 and 32 Hz than for all other values of R. The value of D at threshold was just above 5 RPO for R 8 Hz, consistent with the results of Narne et al (2018) for R ¼ 5 Hz. The median threshold across participants for the condition with static ripples was similar to that reported by Narne et al (2016) and was also similar to the median threshold across participants for the conditions with R ¼ 2-8 Hz.…”
Section: Methodssupporting
confidence: 84%
“…The STRn was generated exactly as described by Narne et al (2016). The carrier was composed of 201 equal-amplitude sinusoidal frequency components, spaced every 0.03 octave from 100 to 6400 Hz.…”
Section: Stimulimentioning
confidence: 99%
See 3 more Smart Citations